Beyond the right to the island: exploring protests against the neoliberalization of nature in Tenerife (Canary Islands, Spain) - Armas-Díaz, Alejandro; Sabaté-Bel, Fernando; Murray, Ivan; Blázquez-Salom, Maciá (ERDKUNDE, 2020)
Islands worldwide experience the commodification of land and natural resources owing to touristic activities and urbanization. Islands represent the epitome of commodified spaces, power, and territorialization. Therefore, focusing on islands reveals how the production of socionatures shapes the dynamics of capital accumulation, dispossession, and resistance. By paying attention to the interplay between insularity and socioecological transformations, we aim at expanding the literature on the neoliberalization of socionatures. We explore the contestation against urban tourism development in Tenerife in recent decades, such as the intense expansion of artificial land use since the touristic boom in mid-20th century, which was intensified through neoliberal capitalism by commodifying elements of everyday life. Environmental struggles inevitably facilitate greater mobilization than other claims. An empirical survey on the spatiotemporal evolution of this island illustrates and helps to deepen the conceptual development of the right to the island and to nature. We found that social contestation and its political emancipatory potential with the defense of nature and the demand for a different social and territorial island model highlights ‘right to nature’ as a central element in the fight for ‘right to the island.’